2008
DOI: 10.1016/j.jeconom.2008.05.010
|View full text |Cite
|
Sign up to set email alerts
|

State dependence in youth labor market experiences, and the evaluation of policy interventions

Abstract: The finding of strong duration dependence in explaining the length of unemployment spells has influenced the design of many labor market policy reforms. However very little work has been done on more complex effects of labor market experiences and in particular on the causal effects of past outcomes involving other labor force states. In this paper we use longitudinal data to investigate the extent of state dependence in labor market outcomes for young Australians. The econometric model estimates the effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 38 publications
4
57
0
Order By: Relevance
“…On the one hand, job changes may allow an upward movement in the career-and wage-ladder and allow youth to become aware of their skills and preferences (Topel and Ward 1992). On the other hand, it has been found that job-changes promote further job-changes (occurrence dependence) and that early job instability significantly reduces later wages (see, e.g., Doiron and Gørgens 2008;Neumark and Wascher 2006). Consequently, ALMP programs should also be measured by their ability to improve the job match quality and stability of accepted employment.…”
Section: The Role Of Active Labor Market Policiesmentioning
confidence: 99%
“…On the one hand, job changes may allow an upward movement in the career-and wage-ladder and allow youth to become aware of their skills and preferences (Topel and Ward 1992). On the other hand, it has been found that job-changes promote further job-changes (occurrence dependence) and that early job instability significantly reduces later wages (see, e.g., Doiron and Gørgens 2008;Neumark and Wascher 2006). Consequently, ALMP programs should also be measured by their ability to improve the job match quality and stability of accepted employment.…”
Section: The Role Of Active Labor Market Policiesmentioning
confidence: 99%
“…We expect a positive relationship between the duration of the previous spell and persistence. On the other hand, path dependence, proxied by the number of previous innovative spells, measures the influence of previous episodes of innovation regardless of their duration (Doiron and Gørgens, 2008). A high number of previous spells should indicates a large number of short innovative episodes, therefore we expect a negative relationship between the number of previous spells and persistence.…”
Section: State-dependent Variablesmentioning
confidence: 97%
“…For example, for graduates from universities of applied sciences, a poor match between education and job after graduation is found to lead to income penalty and worse job satisfaction (Diem, 2015). Unemployment at a young age or after graduation has a significant negative effect on future earnings (Doiron and Gørgens, 2008;Mroz and Savage, 2006;Oreopoulos et al, 2012;Wachter and Bender, 2006). In contrast, stability in the early career and a successful transition from school to work increases future labour-market activity (Neumark and Joyce, 2001) and adult earnings (Neumark, 2002).…”
Section: Other Labour-market Outcomesmentioning
confidence: 99%